Analysis of Sadd adz-Dzari’ah Against the Paradox of "Love" as a Reason for Marriage Dispensation - Kholidiyah Salma; Kasuwi Saiban (JURNAL ILMU SYARIAH, 2026)
The revision of Marriage Law No. 16 of 2019, which sets the minimum age at 19, aims to minimize child marriage. However, national data from 2022-2025 shows an anomaly with high rates of marriage dispensation requests dominated by reasons of "love" and "fear of adultery" (67.16%). This study aims to analyze the shift in the meaning of urgency through the perspective of sadd adz-dzari’ah and to formulate a more protective reconstruction of the dispensation model. Using a qualitative literature study method with an Islamic law approach, this research finds that judges' ijtihad tends to be trapped in preventing presumptive harm (mafsadah mauhumah) such as adultery, while ignoring actual harm (mafsadah muhaqqaqah) such as school dropout and health risks. This causes the function of dispensation to shift from closing the door to harm (sadd adz-dzari’ah) to opening a new door to harm (fath adz-dzari’ah). The results recommend a "Conditional Dispensation" model through mandatory expert involvement and educational integrity pacts to ensure the future welfare of children. Keywords: Marriage Dispensation; Sadd adz-Dzari’ah; Underage Marriage; Maqashid Syariah; Judicial Ijtihad